Hemophagocytic lymphohistiocytosis secondary to epstein-barr virus reactivation in a patient with COVID-19 - Nurfiza Ladak; Kenneth Csehak; Justin Chan; Farnoush Moen (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2022)
Hemophagocytic lymphohistiocytosis (HLH) in coronavirus disease 2019 (COVID-19) is a recognized complication of severe illness. However, this phenomenon has been reported most often in the setting of acute infection. Here we present a case of a patient with a history of severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) infection that subsequently developed HLH weeks after treatment of COVID-19 and discharges from the hospital. Upon re-admission, work-up demonstrated the patient was experiencing Epstein-Barr virus (EBV) reactivation. As EBV infection is a known etiological trigger of HLH, this case provides an alternative mechanism for HLH seen in patients with a history of COVID-19 infection who present after the resolution of acute symptomatology.